CASE STUDY ON GROUNDNUT CULTIVATION IN COASTAL SANDY SOILS IN SPS NELLORE DISTRICT OF ANDHRA PRADESH - KADIRI MOHAN*, U. VINEETHA, T. TULASI LAKSHMI and P. RAJASEKHAR (The Journal of Research ANGRAU, 2020)
The case study was undertaken to document the cultivation practices from seed to seed and issuesrelated to the intensive cultivation of groundnut crop in coastal sandy soils during Rabi season of2018-19. Atotal of around 4000 acres is spread in a single patch of area, wherein, farmers from 10 habitations in threerevenue villages cultivate groundnut as mono crop as their main livelihood since last three decades as acommon group activity. The farmers are following their own groundnut cultivation package of practices triedand tested by themselves to suit their coastal sandy soils ecosystem. The unique cultivation practices thefarmers are following include taking up uniform crop calendar, use of single variety viz., TAG 24,seed rate 200-240 kg of kernels per acre, use of own seed, sowing by seed drill, cent percent seed treatment, use of higherdoses of weedicides, higher rate of fertilizer application, sprinkler irrigation, contract mode of labourfor operationsand sheep penning.Some of the identified constraints as perceived by the farmers include lack of advancedsuitable short duration varieties, lack of recommended package of practices, lack of combined harvester andthreshers, labour shortage during peak season, water shortage during drought years and no storage facility.SWOT analysis indicates some of the important aspects to be strengthened, attended and addressed forsustainable development of groundnut cultivation in the study area.